Implikasi Digitalisasi Layanan Kenaikan Jabatan Akademik dalam Meningkatkan Motivasi dan Kinerja Pengajuan Dosen - Joko Yoeliyanto; Bambang Yulianto; Syunu Trihantoyo; Gunarti Dwi Lestari; Wildan Taufik Raharja (Universitas Negeri Surabaya, 2026)
This article examines the digitalization of academic promotion services at Universitas Negeri Surabaya as part of a broader transformation of administrative processes and the strengthening of academic human resource governance. Although various higher education institutions have implemented digital systems for academic promotion, existing studies largely focus on technical effectiveness or user satisfaction, while limited attention has been given to how such digitalization is experienced by lecturers and how it influences their motivation and performance within complex bureaucratic environments. This study addresses this gap by analyzing how the use of a digital academic promotion information system affects lecturers’ motivation and the performance of promotion proposal submissions. Using a descriptive qualitative approach, data were collected through in-depth interviews with 12 lecturers at Universitas Negeri Surabaya who had utilized the digital academic promotion system, complemented by document analysis of relevant institutional policies and procedures. The data were analyzed thematically to capture lecturers’ experiences, perceptions, and adaptation strategies in responding to the digitalized service. The findings indicate that the digitalization of academic promotion services contributes to increased lecturer motivation through perceived ease of use, procedural clarity, and transparent feedback mechanisms. At the same time, it improves submission performance in terms of timeliness, document completeness, and a reduction in administrative errors. These results suggest that the academic promotion information system not only accelerates administrative processes but also functions as a strategic instrument for more structured, transparent, and professional academic career management within Universitas Negeri Surabaya.